2008
DOI: 10.1021/cg700954t
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Crystallinity of Fluticasone Propionate

Abstract: Solubilization of fluticasone propionate (FP) was effected using aqueous solutions of (i) different grades of poly(ethylene glycol) (PEG), (ii) methanol, and (iii) acetone to enable antisolvent crystallization by the addition of water. The solubility of FP in acetone was significantly higher than in PEG 400 or PEG 6000, and FP solubility was observed to be nonideal in either cosolvent. Crystallization of FP was instantaneous upon addition of water as antisolvent, with nucleation occurring during the mixing pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…The differences identified between the density values and the reproducibility of density determinations by pycnometry for all SX microparticle batches as well as FP PEG 400, FP PEG 6000 and mFP batches, were within ranges identified in previous studies of micronized particles (24). The value for FP PEG 400B were significantly different to the other FP microparticles, however, it was confirmed that the material was of an identical polymorph to all other batches (25).…”
Section: Microparticle Characterizationsupporting
confidence: 78%
“…The differences identified between the density values and the reproducibility of density determinations by pycnometry for all SX microparticle batches as well as FP PEG 400, FP PEG 6000 and mFP batches, were within ranges identified in previous studies of micronized particles (24). The value for FP PEG 400B were significantly different to the other FP microparticles, however, it was confirmed that the material was of an identical polymorph to all other batches (25).…”
Section: Microparticle Characterizationsupporting
confidence: 78%
“…4 show sharp diffraction peaks associated with micronised FP, micronised SX and combination drug particles of FP/SX, which suggest that the materials were predominately crystalline. The XRPD diffractograms of micronised FP and SX are similar to those reported previously (23,26). The XRPD diffractogram of combination drug particles of FP/SX possessed similar peaks to micronized FP, which was to be expected as the combination drug particles of FP/SX contain a significantly greater amount of FP than SX.…”
Section: Physicochemical Characterisationsupporting
confidence: 86%
“…7b) and c). After comparison with literature evidence, metastable form II particles were obtained after the SAS process, while the original particles were analyzed as stable form I [26,39]. The SAS process favored the production of metastable polymorph owing to higher supersaturation and fast nucleation.…”
Section: Resultsmentioning
confidence: 99%